2000
DOI: 10.1002/cd.23220009007
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the development of artistic style in children's artworlds

Abstract: We develop the proposition that children's drawing style is sustained and developed in "artworlds"-a symbolic reality constrained by social valuings of art and opportunities to do art, as well as children's personal themes and representational skills that change systematically over development and with artistic experience.Looking for the Development of Artistic Style in Children's ArtworldsIn this chapter we explore persistence and change in children's artistic style, specifically their style in graphic media.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Judges were also able to recognize new drawings by the same two children drawn at the same time as well as 9 months later. An even stronger demonstration that children have persistent drawing styles was reported by Pufall and Pesonen (2000) who found that adults who learned to recognize the style of three 5-year-olds could identify drawings by these children done 4 years later. But Watson and Schwartz (2000) showed that only about a third of the children in their sample showed a distinctive style, with younger ones (5-to 8-year-olds) showing greater distinctiveness than older children (9-to 10-year-olds).…”
Section: Aesthetic Properties: Expression Composition Style and Colormentioning
confidence: 91%
“…Judges were also able to recognize new drawings by the same two children drawn at the same time as well as 9 months later. An even stronger demonstration that children have persistent drawing styles was reported by Pufall and Pesonen (2000) who found that adults who learned to recognize the style of three 5-year-olds could identify drawings by these children done 4 years later. But Watson and Schwartz (2000) showed that only about a third of the children in their sample showed a distinctive style, with younger ones (5-to 8-year-olds) showing greater distinctiveness than older children (9-to 10-year-olds).…”
Section: Aesthetic Properties: Expression Composition Style and Colormentioning
confidence: 91%
“…These contexts involve support and art-making materials, along with training techniques offered by others, pictorial models, and artistic norms shared by the broader community—all working in concert with the child's individual efforts (Golomb, 2002). Pufall and Pesonen (2000) discussed these contexts in terms of artworlds (Becker, 1982, cited in Pufall & Pesonen, 2000), or social environments that entail the people, physical spaces, and tools supporting artistic creation and provide artistic themes and styles.…”
Section: Competing Explanations Of Semiotic Developmentmentioning
confidence: 99%